CYTOGENETIC PROFILE OF ACUTE LYMPHOBLASTIC LEUKAEMIA PATIENTS AND ITS ASSOCIATION WITH INDUCTION REMISSION STATUS - Niaz, Hina; Hamid Saeed Malik; Rafia Mahmood; Asad Mehmood; Umarah Nisar; Saniya Jalil (Journal of Ayub Medical College Abbottabad, 2022)
Background: To determine the cytogenetic abnormalities in patients of Acute Lymphoblastic Leukaemia as a predictor of response to induction chemotherapy.It was a descriptive cross sectional study. Methods: This study was conducted at the Armed Forces Institute of Pathology, Rawalpindi over a period of six months from June to November 2019. Bone marrow and peripheral blood samples of newly diagnosed 80 patients of all the age groups and either gender, who received one month treatment for ALL,were analyzed for cytogenetic study. Patients who were previously diagnosed with ALL, who presented with relapse and those who required induction treatment outside the trial hospital were excluded. UK ALL 2011 treatment protocol was adopted for patients up to 25years old and for patients above 25years old UK ALL 2014 treatment protocol as induction chemotherapy was adopted. Evaluation for remission was carried out at the termination of initial induction chemotherapy on day 29 of treatment. Results: A total of 80 patients were enrolled in the study, comprising 36(45%) females & 44(55%) males. The median age of paediatric patients was 5years (<19 years) who were 56/80(70%) in number whereas the median age of adults was 27 years (>19 years) who constituted 24/80 (30%) of the participants. Cytogenetic of 51(63.75%) patients revealed hyperdiploidy (chromosome number 51-66) whereas 29(36.25%) of the participants had miscellaneous mutations [(Hypodiploidy, t (9; 22), t (1; 19) and t (12; 21)]. On immunophenotyping 51/80 (63.7%) of the leukemias were of B cell origin and 29(36.25%) of T-cell origin.Conclusion: Patients with hyperdiploidy, t(12;21)ETV6/RUNX1 and t(1;19)TCF3/PBX1 had better prognosis and higher remission rate compared to those with the other mutations like t(9;22)Ph+ and hypodiploid which were associated with poor prognosis. Association of gender with remission was not statistically significant.